KINERJA LAPANGAN PENUMPUKAN STASIUN JAKARTA GUDANG PT KERETA API INDONESIA - Fernaldi Anggadha Pratama; Tri Mulyono (LOGISTIK, 2019)
By collecting data in primary and secondary forms, namely in the form of direct observation around the stacking field at the Jakarta warehouse station regarding the capacity of the piling field in the form of notes about the situation and conditions in the field, conducting direct interviews with employees of PT Kereta Api Indonesia and the forwarders and recap loading and unloading months June, which was carried out by the author during the Fieldwork Practices (PKL). The data obtained are then analyzed to determine the Yard Occupancy Ratio. The high average use of stacking yards that is not in accordance with the loading and unloading performance and high container deposition can affect the Yard Occupancy Ratio itself. Thus, it is necessary to carry out routine supervision in the stockpiling field and to find out which containers have passed the stockpiling period at the warehouse in Jakarta Station.